Investigation of histopathological alteration of paramyxovirus-1 in naturally infected racing pigeons - Ayman A. Al-Alhially; Entisar K. Al-Hamdany; Hana Kh. Ismail (Iraqi Journal of Veterinary Sciences, 2024)
The current study aimed to investigate the infection of racing pigeons with paramyxovirus-1(PMV-1) based on clinical signs of histological and histochemical changes, which increase the mortality rate in flocks called pigeons paramyxovirus. The study samples were collected from 45 birds from different Mosul city regions suffering from neurological signs considered pathological signs of paramyxovirus infection, like tremors, ataxia, leg and wing paralysis, and torticollis. The study collected some organs from birds most affected by infection with paramyxovirus. They include the heart, brain, liver, and kidneys. Grossly, brain lesions represented 66.6%, heart lesions represented 37.7%, liver lesions represented 55.5%, and kidney lesions represented 42.2%, respectively. The histological examination of these organs showed many histological changes represented by degenerative, necrotic, and inflammatory changes in all the tissue studied, in addition to the presence of vascular changes and fibrosis in some sections. In contrast, the section stained with Masson’s trichrome showed severe deposition of collagen fibers in liver and heart tissues. The conclusion of the current study represented the histopathological histochemical changes in naturally infected racing pigeons with PMV -1. pigeons are considered a serious victim of the virus, which replicates in all body organs, since it is considered a severe threat and problem to poultry flocks.